The problem of youth in the works of Alash intellectuals - Beisenbekova, N.; Nupinova, Zh. (KSU publ., 2019)
In this article, the author on the basis of the proposal of the First President of the Republic of Kazakhstan Nursultan Nazarbayev to declare 2019 the «Year of youth», stressing the importance of holding a special forum «Youth is our future» on January 23, 2019, says that youth today is our reliable support in tomorrow, which will implement good deeds in the development of the national state. At the same time, today's youth must become competitive. In the beginning, according to the author, today's Kazakh society contributes to the development of youth. The main provisions and conclusions of the article may be of interest to a wide range of specialists-historians, international relations, linguists. From the point of view of the national position on youth, special attention in the historical works of the Kazakh intelligentsia is paid to the problems of youth. In addition, during the implementation of the program «Rukhani Zhangyru» great practical importance is the use in the work of young teachers, educators, employees working in youth centers. The works of the Kazakh intelligentsia are useful for writing scientific papers of students, undergraduates.
Keywords: Alash intellectuals; the youth; education; independence; the nation; young people; works